Evaluation of the mechanical properties of AA 6063 processed by severe plastic deformation - Jafarlou, D.M.; Zalnezhad, E.; Hamouda, A.S.; Faraji, G.; Bin Mardi, N.A.; Mohamed, M.A.H. (Springer Verlag (Germany), 2015)
In this study, the mechanical properties, including surface hardness, tensile strength, fatigue, and fretting fatigue behavior of AA 6063 processed by equal channel angular pressing as the most efficient severe shear plastic deformation (SPD) technique, were investigated. Following the SPD process, samples were subjected to heat treatment (HT), hard anodizing (HA), and a combination of HT and HA. Rotating-bending fretting fatigue tests were performed to explore the samples' response to the fretting condition. From the experimental fatigue and fretting fatigue tests, it was apparent that the SPD treatment had a positive effect on enhancing the fatigue and fretting fatigue lives of the samples at low and high-cyclic loads compared with the HT technique by 78 and 67 pct, and 131 and 154 pct respectively. The results also indicate that the SPD + HT technique significantly increased the fatigue and fretting fatigue lives of the samples at high and low cycles by 15.56 and 8.33 pct, and 14.4 and 5.1 pct respectively, compared with the SPD method. HA of AA6063 increased the fatigue and fretting fatigue lives of SPD + HT-processed samples at low cycle by 15.5 and 18.4 pct respectively; however, at high cycle, HA had reverse effects, whereby the fatigue and fretting fatigue lives of SPD + HT-processed samples decreased by 16.7 and 30 pct, respectively. (C) The Minerals, Metals & Materials Society and ASM International 2015